Akuntansi Manajemen Syariah dan Konstruksi Sosial (Sebuah Studi Literatur) - Aziz, Fathul Aminudin (IAIN Kudus, 2019)
In the reality of life, management accounting has many variables related to social aspects through the basic assumptions of behavior by looking at the Islamic world. The purpose of this study is to make a construction of Islamic management accounting with the social aspects of Muslim behavior. This research is literature research. The principle used in this discussion is to